Modality Therapy : Calisthenics for Elderly with Hypertention In Tanipah Village - Milasari Milasari; Anita Agustina; Yosra Sigit Pramono; Muhammad Rauf; Dewi Kartika Wulandari (UrbanGreen Central Media, 2022)
Along with the success of the government in national development, especially in the health sector, it has resulted in improving the health of the population and increasing life expectancy. The Central Bureau of Statistics shows that the population of the elderly in Indonesia in 2008 was 8.55% of the total population. The increase in the number of elderly people must also be balanced by an increase in the quality of health. There are various health problems, one of which is the case of hypertension. An effort that can be made to help reduce the problem of hypertension in the elderly is by modality therapy for elderly exercise. From the survey results obtained from 10 elderly people, 5 of them suffer from hypertension in Tandipah Village, RT 03. And some of the elderly say that they have not optimally participated in these activities because the elderly's awareness of the benefits of these actions is not maximized in an effort to reduce blood pressure. The community includes the implementation of gymnastics therapy for the elderly with hypertension which involves all the elderly in Tanipah RT 03 assisted by all cadres and village officials. Result: Implementation of community service takes place according to the plans that have been made. Gymnastics is carried out using gymnastics video media and with the demonstration method